Teaching and Education highlighted. Issue 2 (4th April 2022) - Dawe, Louise N.; García-Ruiz, Juan Manuel; Hadju, Janos; McIntyre, Garry J.; Meilleur, Flora; Stephenson, Lisa
Abstract : The development of the Teaching and Education (T&E) category of articles in Journal of Applied Crystallography, leading to the recent appointment of Louise Dawe as an additional T&E Editor, is described. Louise and ongoing T&E Editor Juan Manuel García‐Ruiz outline their vision for the category. Abstract : The development of the Teaching and Education (T&E) category of articles in Journal of Applied Crystallography, leading to the recent appointment of Louise Dawe as an additional T&E Editor, is described. Louise and ongoing T&E Editor Juan Manuel García‐Ruiz outline their vision for the category.